2014
DOI: 10.3109/02713683.2014.967869
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of X-Linked Hypohidrotic Ectodermal Dysplasia by Meibography and Infrared Thermography of the Eye

Abstract: Meibography is the most reliable ophthalmic examination to establish a clinical diagnosis in individuals with suspected hypohidrotic ectodermal dysplasia, even before genetic test results are available. Tear film tests and ocular surface staining are less sensitive in children, but very helpful for estimating the severity of ocular surface disease in individuals with known XLHED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
1
7
0
2
Order By: Relevance
“…Meibomian glands produce the lipid portion of the tear film that slows down evaporation and subsequently prevents dry eye (Arita et al, 2017). These glands are greatly reduced or absent in humans (Kaercher et al, 2015), mice (Gaide and Schneider, 2003), and dogs (shown here) with XLHED. Therefore, dry eye requiring daily lubrication is a significant problem found in affected patients, with development of corneal lesions and scarring if left untreated in humans (Dietz et al, 2013) and dogs (Casal et al, 2007).…”
Section: Discussionmentioning
confidence: 71%
“…Meibomian glands produce the lipid portion of the tear film that slows down evaporation and subsequently prevents dry eye (Arita et al, 2017). These glands are greatly reduced or absent in humans (Kaercher et al, 2015), mice (Gaide and Schneider, 2003), and dogs (shown here) with XLHED. Therefore, dry eye requiring daily lubrication is a significant problem found in affected patients, with development of corneal lesions and scarring if left untreated in humans (Dietz et al, 2013) and dogs (Casal et al, 2007).…”
Section: Discussionmentioning
confidence: 71%
“…Of the >170 clinically defined ectodermal dysplasias (Priolo and Lagana 2001; Visinoni et al 2009; Pagnan and Visinoni 2014), X-LHED is most frequently observed (Schneider et al 2011; Fete et al 2014; Kaercher et al 2015). Genetic mutations in EDA disrupt EDA signaling, which results in hypoplastic development of epithelial tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Although representing no improvement on current practice, IRT illustrated marked temperature differences between children with XLHED and the healthy controls and was shown to be a quick and reliable tool to be used in conjunction with other methods of diagnosis. 36 …”
Section: Irt In Childrenmentioning
confidence: 99%